Pilot phase trial to quantify the extent and relevance of any deepwater puerulus settlement that may have taken place in the Western Rocklobster Fishery - Winzer, A.; de Lestang, S.; Melville-Smith, Roy (Fisheries Research and Development Corporation, 2010)
This study had two objectives. Firstly to trial modifications to commercial western rock lobster pots, so as to sample as wide a size range of lobsters on the grounds as possible. Sampling took place over a 10 day period between 13-24 September 2009, with seven commercial fishermen being responsible for collection of the data at different sampling locations (Mandurah, Fremantle, Lancelin, Dongara, Geraldton, Abrolhos and Kalbarri). This arrangement proved to be successful in that a wide area of the coast was covered by the sampling regime and good quality catch composition data was achieved across the four depth zones (0-10 fm, 10-20 fm, 20-30 fm and >30 fm) that were sampled. The different pot modifications that were trialled sampled a wide size range (25-144 mm CL), but mostly caught lobsters around the legal size limit (modal size, 80 mm CL). In three of the four areas where more than one pot type was used, there were significant differences (p<0.01) in the catch rates of one or more size classes between the various pot types.The second objective was to establish whether there has been a shift in post-puerulus settlement from shallow to deeper waters. Analysis showed that depth was highly significant (p<0.05) in determining the catch rates of most size classes (≤50 mm CL; 51-65 mm CL; 66-76 mm CL; 77-105 mm CL and ≥105 mm CL). Generally, small size classes were sampled in the shallow depth categories and larger lobsters were sampled in the deeper depth categories, which would suggest that as in the past, recent puerulus settlement has been in shallow depths. Accordingly, it would seem reasonable to conclude that it is unlikely that there has been a major shift in the depths at which pueruli are settling. However, small lobsters were sampled in low numbers in the deep water categories in this survey and this therefore does not exclude the possibility that deep water settlement may be becoming more common than in past.In terms of recommendations, more monitoring of post-puerulus/juvenile lobsters using modified commercial pots similar to those used in this study has the potential to provide inter-annual comparisons of the numbers of small size classes settling at different depths on the grounds. It is only with more data of this type over a longer time period, that it will be possible to show whether there is any indirect evidence of a shift in settlement to deeper water. Should this work continue into the future, it would be beneficial to standardize on a consistent type of modification to the commercial pots so that more reliable comparisons of the relative numbers of juvenile animals can be made between areas.